The Income of Business Snack Video Application on the Covid-19 Pandemic toward Islamic Economic Law Perspective in Bukittinggi - Wadi, Fajrul; Hendri, Hendri (ADDIN, 2022)
In this research, there are two issues that are studied, firstly how is the business practice of Snack Video applications during the Covid-19 pandemic, secondly how is the perspective of Islamic economics law on the practice and income of the Snack Video application business. Researchers use the field method (field research). This research is qualitative research, then the data is described, analyzed, and discussed to answer these problems. So from the results of the study, it was found that the implementation of the Snack Video application business during the Covid-19 pandemic in Bukittinggi had there aspects, how to use the Snack Video application, how to exchange coins and become money from the Snack Video application and the motivation to use the Snack Video application was in accordance with the provisions. The Snack Video application and in accordance with the provisions of Islamic economy, which is not contrary to Islamic economy, as for cashing out the coins generated from the Snack Video application, it can be disbursed through the application. Money accepted by users is sourced from the company Joyo Technology, Pte. Ltd. and this is mutually beneficial for both parties. According to Islamic law, the contract on Snack Video application consisted of ijarah contract and juala contract which includes 4 missions to get coins that can be exchanged in the form of money. This contract is allowed so that the income earned from the Snack Video application business is included in the jaizah (allowed).